2022
DOI: 10.1111/ene.15229
|View full text |Cite
|
Sign up to set email alerts
|

Association of symptomatic atherosclerotic carotid arteries with plaque areas showing low densities on computed tomographic angiography

Abstract: Background and purpose Intraplaque hemorrhage is a key feature of vulnerable carotid atherosclerotic plaque (CAP), associated with low densities (<25 Hounsfield units [HU]) on computed tomographic angiography (CTA). This study aimed to analyze CAP on routine CTA performed in patients with symptomatic and asymptomatic carotid stenosis undergoing carotid endarterectomy (CEA) by assessing HU of the CAP area showing the lowest density (CAPALD) using radiological tools available in daily clinical practice, and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A previous study revealed that symptomatic carotids are associated with carotid atherosclerotic plaque areas with low densities on CTA, which may be useful for identifying vulnerable plaques at risk for future stroke. 29 Our results showed that PVAT radiodensity is an independent predictor of ACP, with OR of 1.263, and is independent predictors of MPBS and plaque density, with β-coefficient of .073 and −1.666, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…A previous study revealed that symptomatic carotids are associated with carotid atherosclerotic plaque areas with low densities on CTA, which may be useful for identifying vulnerable plaques at risk for future stroke. 29 Our results showed that PVAT radiodensity is an independent predictor of ACP, with OR of 1.263, and is independent predictors of MPBS and plaque density, with β-coefficient of .073 and −1.666, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…While the latest literature points out that low densities (<25 HU) on CTA seem to indicate IPH. Compared with asymptomatic plaques, HU values of <25 are frequently observed in symptomatic plaques [ 157 ]. CTA can also identify and quantify neovascularization.…”
Section: Identification Of Vulnerable Plaques At the Macroscopic Levelmentioning
confidence: 99%